An investigation into whether a leadership and management development project changed the perceptions of the educators in a black, disadvantaged school - Jaftha, A P (Rhodes University, Faculty of Education, Department of Education, 2003)
This study investigates whether a leadership and management development programme changed the management perceptions of the teachers of one of the schools that participated in the programme. The programme seeks to change the organisational culture of schools and develop effective management. The development philosophy of the programme is informed by literature on school effectiveness, organisation development, whole school development and systemic change. My research is conducted in the interpretive paradigm. Interpretive researchers view reality a construct of the human mind, and therefore the way people perceive the world is not necessarily the same since there can be different understandings of what is real. I employ convenience sampling to select the school and purposive sampling to identify my research participants. Whilst overall impression that the data conveys is that much of the programme does not seem to have had a lasting effect on the culture of the school, it nonetheless made an impression on the teachers' perceptions of management. There clearly seems to be a greater appreciation of participative management processes. The reintroduction of proper prior planning played a decisive role in re-establishing sound work ethics at the school and contributes to a more structured approach to events at the school. Some sort of organisational learning has also been introduced at the school. The realisation on the part of the staff that they now have their destiny in their own hands is an especially critical development. And whilst the vision is not a compelling force in the organisation, it has nevertheless produced some strategic focus at the school. The insights and skills they acquired concerning resource management will also stand them in good stead.
Keywords: University of Port Elizabeth -- Institute for Development Planning and Research; Delta Foundation -- Centres of Learning; School management and organization -- South Africa; Educational leadership -- South Africa; Educational change -- South Africa